IMPROVING THE METHODOLOGY FOR DEVELOPING STUDENTS’ DIGITAL PEDAGOGICAL-CREATIVE COMPETENCE IN PROBLEM-BASED TEACHING OF PEDAGOGICAL SCIENCES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses the development of digital pedagogical and creative competencies in future primary school teachers within the digital learning environment, particularly during the process of mastering pedagogical subjects such as mathematics and its teaching methodology. It analyzes the concept of digital-creative competence, its importance in the professional activity of teachers, and the role of modern information and communication technologies (ICT) in its development. Additionally, the article outlines ways to enhance students’ independent learning, creativity, and methodological thinking skills by integrating digital resources into the learning process.